2021
DOI: 10.3390/pathogens10050528
|View full text |Cite
|
Sign up to set email alerts
|

Unique Attributes of the Laurel Wilt Fungal Pathogen, Raffaelea lauricola, as Revealed by Metabolic Profiling

Abstract: Raffaelea lauricola is the causative agent of laurel wilt, a devastating disease of lauraceous trees. R. lauricola is also an obligate nutritional symbiont of several ambrosia beetle species who act as vectors for the pathogen. Here, we sought to establish the baseline “phenome” of R. lauricola with knowledge concerning its metabolic capability, expanding our understanding of how these processes are impacted by environmental and host nutrients. Phenotypic screening using a microarray of over one thousand compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Susceptible trees begin to show symptoms within 2 weeks after infection and can die as early as 4 to 6 weeks post‐infection (Hughes et al, 2015a). Although the complete pathology of H. lauricola infection is still unknown, metabolic profiling is beginning to reveal the underlying mechanisms in susceptible hosts (Joseph et al, 2021). For a thorough review of the X. glabratus , H. lauricola , and laurel wilt systems, see Ploetz, Kendra, Choudhury et al (2017) and Olatinwo et al (2021).…”
Section: Introductionmentioning
confidence: 99%
“…Susceptible trees begin to show symptoms within 2 weeks after infection and can die as early as 4 to 6 weeks post‐infection (Hughes et al, 2015a). Although the complete pathology of H. lauricola infection is still unknown, metabolic profiling is beginning to reveal the underlying mechanisms in susceptible hosts (Joseph et al, 2021). For a thorough review of the X. glabratus , H. lauricola , and laurel wilt systems, see Ploetz, Kendra, Choudhury et al (2017) and Olatinwo et al (2021).…”
Section: Introductionmentioning
confidence: 99%
“…examination(Joseph et al 2021). However, effective methods for controlling the movement of X. glabratus and other vectors are very limited(Rivera et al 2020), and there are few effective treatments for trees infected with H. lauricola(Olatinwo et al 2021).…”
mentioning
confidence: 99%
“…For inoculum preparation, the FF inoculum fluid proposed by Biolog TM for filamentous fungi Pertile et al, 2020) and the PM3.5-8 inoculum fluid (Joseph et al, 2021) that, as previously demonstrated, are adequate for the evaluation of fungal response in microplate functional assays, were compared. In addition to the inoculum fluid and the type of indicator compound, it was necessary to test different concentrations of a nitrogen source.…”
Section: Discussionmentioning
confidence: 99%